2012
DOI: 10.1248/bpb.b12-00579
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Prevents <i>in Vitro</i> Aggregation of Slightly Negatively-Charged Liposomes Induced by Heparin in the Presence of Bivalent Ions

Abstract: Liposomes are of great interest as drug delivery vehicles, and studies have focused on understanding how the physical and chemical characteristics of liposomes can be modified to improve their in vivo behavior. In a previous study, we found that the slightly negatively-charged liposomes aggregate only in the culture medium of human umbilical vein endothelial cells, whereas the liposomes modified with polyethylene glycol (PEG) (PEGylated) did not aggregate. In the present study, we investigated the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The maintenance of the mean diameter over time may have been due to the highly negative surface charge and the presence of PEG chains on the liposome surface, which could have prevented vesicle aggregation through steric repulsion, improving the stability of the formulations. 26,27 These results are in agreement with those previously reported by Lopes et al, using a similar liposomal composition. 28…”
Section: Storage Stabilitysupporting
confidence: 93%
“…The maintenance of the mean diameter over time may have been due to the highly negative surface charge and the presence of PEG chains on the liposome surface, which could have prevented vesicle aggregation through steric repulsion, improving the stability of the formulations. 26,27 These results are in agreement with those previously reported by Lopes et al, using a similar liposomal composition. 28…”
Section: Storage Stabilitysupporting
confidence: 93%
“…refs 45 , 46 . Approaches have been reported by which aggregation may be avoided, for example via coating of the liposomes with steric inhibitors, such as polyethylene glycol 47 . This approach, however, might hinder the investigated interaction.…”
Section: Resultsmentioning
confidence: 99%
“…It was generally understood that liposomes with zeta potentials either in excess of ?30 mV or below -30 mV remain stable in the aqueous phase. In addition, it was demonstrated that PEG modification can prevent in vitro aggregation of negatively charged liposomes [28]. Therefore, the stability observed for Bar/HP-b-CD/liposome suggests that the liposomal inclusion complex of Bar meets the requirement for a potentially viable drug delivery system.…”
Section: Discussionmentioning
confidence: 98%